Reformulation of Criminal Act of Corruption in Building Failure Within Procurement of Construction Services from Perspective of Legal Certainty - F. Dirun, Wikarya; Syaufi, Ahmad; Faishal, Achmad; Suprapto, Suprapto (Journal of Progressive Law and Legal Studies, 2025)
Infrastructure development is a strategic sector in national development as mandated by the 1945 Constitution of the Republic of Indonesia and regulated under Law Number 2 of 2017 on Construction Services. However, the practice of law enforcement concerning building failures demonstrates inconsistency, particularly when applying the Anti-Corruption Law (UU Tipikor), despite such matters being more appropriately resolved through the legal mechanisms of construction law or civil contract law. The collapse of the Mandastana Bridge and the Sukamara Prison wall serve as concrete examples of legal uncertainty arising from improper application of the law, thereby raising issues of legality, the principle of ultimum remedium, and legal certainty. This study aims to analyze the application of Article 2 Paragraph (1) and Article 3 in conjunction with Article 18 of the Anti-Corruption Law and Article 55 Paragraph (1) of the Indonesian Criminal Code (KUHP) in relation to building failures in government goods and services procurement; to examine its legal implications; and to formulate an ideal, logical, consistent, and harmonious legal policy within the national legal system. Utilizing a normative approach, the research affirms that building failures are more effectively addressed through administrative and civil instruments, except where clear indications of corruption exist. The findings indicate that multiple interpretations of the elements of “unlawfulness,” “self-enrichment,” and “state loss” in the Anti-Corruption Law result in inconsistent law enforcement, protracted legal processes, and hesitation among officials in making decisions. Therefore, legal reform is required through the revision of the Anti-Corruption Law, the drafting of technical guidelines, capacity-building for law enforcement, and the protection of official discretion in accordance with the principles of good governance. Thus, a reconstruction of construction law focused on justice, legal certainty, and public benefit is expected to deliver infrastructure that is high-quality, sustainable, and capable of providing optimal economic benefits for society.